2001
DOI: 10.1007/s00022-001-8577-x
|View full text |Cite
|
Sign up to set email alerts
|

The Radon-split and the Helly-core of a point configuration

Abstract: We provide a systematic construction of point configurations with incompatible Radon-split and Helly-core. This provides a resolution of problems of Reay and Sierksma, and shows that it is computationally hard to decide the compatibility of the split and core of a configuration. (2000): 05A, 05B, 05C, 51M, 52A, 52B, 52C, 68Q, 68R, 68U, 90B, 90C. Mathematics Subject Classifications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Associate with every edge {v i , v j } in G its characteristic vector in R d , giving a configuration Conf(G) of 3n/2 points in (n − 1)-dimensional space. In [Onn01] and also in personal communication (2011), Onn observed that the existence of a Tverberg 3-partition (or even of a Reay (3,2)-partition; see Section 6.2) is equivalent to a 3-edge coloring for G, and he concluded that deciding if a configuration of 3(d + 1)/2 points in R d (d an odd integer) admits a Tverberg partition into three parts is NP-complete.…”
Section: Radon Partitions and Radon Points For Configurations Based O...mentioning
confidence: 99%
“…Associate with every edge {v i , v j } in G its characteristic vector in R d , giving a configuration Conf(G) of 3n/2 points in (n − 1)-dimensional space. In [Onn01] and also in personal communication (2011), Onn observed that the existence of a Tverberg 3-partition (or even of a Reay (3,2)-partition; see Section 6.2) is equivalent to a 3-edge coloring for G, and he concluded that deciding if a configuration of 3(d + 1)/2 points in R d (d an odd integer) admits a Tverberg partition into three parts is NP-complete.…”
Section: Radon Partitions and Radon Points For Configurations Based O...mentioning
confidence: 99%
“…Equality was conjectured [28,31], and actually holds when d = 2 or m = 1. However, Avis found a counterexample for n = 9, d = 3 and m = 3 [1], and Onn provided a systematic construction for counterexamples [26].…”
Section: Theorem Bmentioning
confidence: 99%
“…Equality was conjectured [Rea82,Sie82], and actually holds when r = 2 or κ = 1. However, Avis found a counterexample for n = 9, r = 3 and κ = 3 [Avi93], and Onn provided a systematic construction for counterexamples [Onn01].…”
Section: Tverberg's Theorymentioning
confidence: 99%